2012
DOI: 10.1021/ma202783p
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting POSS–Sorbitol Interactions: Issues of Reinforcement of Isotactic Polypropylene Spun Fibers

Abstract: This study investigates the issues involving reinforcement of isotactic polypropylene (iPP) spun fibers by molecular adducts originating from the synergistic interactions of polyhedral oligomeric silsesquioxane (POSS) containing silanol functionalities (silanol–POSS) and di(benzylidene)sorbitol (DBS). The molecular adducts of silanol–POSS and DBS were low viscosity liquids at fiber spinning temperature, turned into cylindrical domains during fiber spinning, and remained as nanoparticles in the fibers. The fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 61 publications
0
42
0
1
Order By: Relevance
“…We have demonstrated that even with excellent matches in compatibility between POSS and matrix fillers, often as not the outcome is plasticization or antiplasticization of the polymer [18]. Recent work by Jana and coworkers has further shown that POSS can serve as an effective processing aid in the spinning of polypropylene fibers, increasing mechanical properties not because of composite reinforcement, but rather due to chain slippage and increased ability to orient the polymer during drawing [19]. Such results, combined with the few cases where POSS/polymer systems appeared to hydrogen bond, led us to conclude that high compatibility between POSS and polymer is necessary, but insufficient in order to produce enhanced properties in these heterogeneous systems [20] The present study is an attempt to unify the above results, combined with new data examining confinement of POSS within oriented polymer fibers, in order to generate definitive design rules of use in the blends/composites field.…”
Section: Introductionmentioning
confidence: 85%
“…We have demonstrated that even with excellent matches in compatibility between POSS and matrix fillers, often as not the outcome is plasticization or antiplasticization of the polymer [18]. Recent work by Jana and coworkers has further shown that POSS can serve as an effective processing aid in the spinning of polypropylene fibers, increasing mechanical properties not because of composite reinforcement, but rather due to chain slippage and increased ability to orient the polymer during drawing [19]. Such results, combined with the few cases where POSS/polymer systems appeared to hydrogen bond, led us to conclude that high compatibility between POSS and polymer is necessary, but insufficient in order to produce enhanced properties in these heterogeneous systems [20] The present study is an attempt to unify the above results, combined with new data examining confinement of POSS within oriented polymer fibers, in order to generate definitive design rules of use in the blends/composites field.…”
Section: Introductionmentioning
confidence: 85%
“…Reactive mixtures of POSSs and NAs as well as POSS nanoparticles substituted with commercially used NAs were used to increase NA efficiency and extend the potential field of their application. The incorporation of reactive mixtures consisting of POSSs and NAs into polypropylene matrix was firstly introduced by Roy et al It was proved that formation of molecular complexes, consisting of sorbitol derivatives and phenylsilsesquioxanes, prevented sorbitol fibrillation in iPP matrix upon cooling, which also reduced its nucleation efficiency, and in turn allowed tailoring of crystallization kinetics of iPP by modulating formulation of the modifier. Another system, consisting of silsesquioxane cages functionalized with sodium benzoate, was applied to polypropylene to enhance crystallization of α ‐phase in polypropylene matrix …”
Section: Introductionmentioning
confidence: 99%
“…When the siloxane‐silsesquioxane resin is added to the formulation, the nucleation efficiency of NX8000 is not affected. Both fillers have functional groups that may in principle interact upon melt mixing, by possible establishment of hydrogen bonds, influencing miscibility of the modified sorbitol with polypropylene and in turn, its efficiency as nucleating agent . For all the analyzed compositions containing NX8000 and various amounts of SiOPh, the onset temperature is not affected by SiOPh, as shown in Figure (b).…”
Section: Resultsmentioning
confidence: 88%
“…Despite all these advantages, it was shown that these organic–inorganic hybrids are poorly compatible with iPP . An alternative approach consists of combining commercially used nucleating agents with organic–inorganic materials . Roy et al .…”
Section: Introductionmentioning
confidence: 99%